Conflict, adaption, and strategic defiance: service providers’ roles in constructing prisoner reentry through role adaption - Whittle, Tanya N. (Journal of crime and justice, 2018)
This research explores how service providers experience their work and influence prisoner reentry services. This paper builds on prior knowledge of street-level bureaucrats’ roles and discretionary decisions. Data are derived from 35 in-depth interviews of service providers who work with currently and previously incarcerated people and 240+ h of observations at pre- and post-release reentry assistance programs and service organizations. Findings show that service providers assume various professional roles and identities. Professional roles correspond to discretionary toolkits that include terminology, goals, and definitions of success. Assumed professional roles and discretionary toolkits help service providers efficiently navigate complex work environments and interactions. This research goes beyond the Rule Enforcer, Social Worker, and Bureaucratic Survivalist/Case Manager professional roles identified in previous research of service providers. Reentry service providers also use an Underground Advocate role while conducting reentry service work. The Underground Advocate role is particularly utilized to adapt to negative work conditions, including competing goals, conflict, and limited resources.